2013
DOI: 10.1128/aac.00424-13
|View full text |Cite
|
Sign up to set email alerts
|

The Perfidious Effect of Topical Placebo: Calibration of Staphylococcus aureus Ventilator-Associated Pneumonia Incidence within Selective Digestive Decontamination Studies versus the Broader Evidence Base

Abstract: Among various methods for preventing ventilator-associated pneumonia (VAP), the evidence base for selective digestive decontamination (SDD) appears most compelling. However, the extent of Staphylococcus aureus emergence with SDD use remains uncertain. Groups from 37 observational studies and component (control and intervention) groups from 58 studies of SDD and other methods of VAP prevention were sourced exclusively from 10 systematic reviews. S. aureus as a proportion of VAP isolates (S. aureus isolate propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 46 publications
1
28
0
Order By: Relevance
“…First, the use of a topical placebo to achieve observer blinding is a key marker of a high-quality study, especially where the endpoint is somewhat subjective, as is the case for VAP. However, approximately half of the studies of topical polymyxin used a topical placebo to achieve observer blinding (27). The PsVAP incidences derived from CC studies that were or were not observer blinded were similar.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…First, the use of a topical placebo to achieve observer blinding is a key marker of a high-quality study, especially where the endpoint is somewhat subjective, as is the case for VAP. However, approximately half of the studies of topical polymyxin used a topical placebo to achieve observer blinding (27). The PsVAP incidences derived from CC studies that were or were not observer blinded were similar.…”
Section: Discussionmentioning
confidence: 96%
“…The disparity in the incidence of PsVAP among studies of topical polymyxin versus the respective benchmarks recapitulates similar observations for various endpoints among studies of SOD/SDD versus externally derived benchmarks from populations of MV patients. For example, with respect to Staphylococcus aureus as a VAP isolate (27), Staphylococcus aureus bacteremia (36), Candida as a respiratory tract isolate (37), and candidemia incidence (35), in each case, the endpoint is higher among control groups of SOD/SDD studies than the respective benchmarks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of observer . Note that studies that used candidemia risk factors as a basis for patient selection are not shown and the y-axis is a logit scale blinding may be confounded by the separate effect of topical placebo in this context [28].…”
Section: Discussionmentioning
confidence: 99%
“…In each case, the increased incidence within control groups of CC design studies of topical antibiotics remains apparent in meta-regression models adjusting for other recognized associations. The influence of topical placebo use, concurrent colonization with Candida, and other influences may also have influences in this process [45][46][47].…”
Section: Limitationsmentioning
confidence: 99%